Hubungan Pengetahuan Tentang Mencuci Tangan Sebelum Makan dengan Kejadian Kecacingan pada Anak di SDN 040517 Tigajumpa Kecamatan Barusjahe Kabupaten Karo Tahun 2021 - Juli Evianna br. Purba (Pusat Riset dan Inovasi Nasional, 2023)
In Indonesia, due to poor environmental sanitation, worm sufferers will gradually become malnourished. According to WHO in 2017, more than 270 million preschool-age children and more than 600 million school-age children lived in areas infected with worms. The aim of this research is to determine the relationship between knowledge about washing hands before eating and the incidence of worms in children at SDN 040517 Tigajumpa, Barusjahe District, Karo Regency in 2021. Worms or intestinal worms are a collection of symptoms of health problems due to the presence of parasitic worms in the body. With the Independent Variable, namely elementary school children's knowledge about washing their hands. and the Dependent Variable is the incidence of worms. The type of research used was analytical observational with a cross sectional approach method where the population was 40 people and the sample was 30 people using a total sampling technique. The type of data used is primary data taken directly from respondents using a questionnaire, and secondary data obtained from the principal of SDN 040517 Tigajumpa. The statistical test used is the chi-square test α=0.05. Based on the research results, it was found that the majority of elementary school children's knowledge about washing their hands before eating was 65% and those who had never experienced worms were 35%. The results of the Chi-Square statistical test obtained a value of p = 0.00. This means that the p value is smaller than α (0.05), which means there is a relationship between elementary school children's knowledge and the incidence of worms. and thus Ha is accepted and Ho is rejected, namely there is a relationship between knowledge and the incidence of worms. It is recommended for children who attend school at SDN 040517 Tigajumpa, Barusjahe District, Karo Regency to cultivate the habit of washing their hands before eating, wearing footwear, cutting their nails and regularly taking worm medicine every six months to prevent worms.